“ENHANCING CRITICAL THINKING SKILLS BY USING THE REVISED BLOOM’S TAXONOMY - THE COGNITIVE DOMAIN” - Muhammad Sulhan (Deiksis, 2011)
We all know that Bloom’s Taxonomy consists of three domains of educational goals and objectives; (1) Cognitive Domain, (2) Affective Domain, and (3) Psychomotor Domain. The major idea of this taxonomy is the process of thought which educators expect from students to emerge based on the educational objectives from less to more complex. This paper is a discussion of theories suggested by education experts who have dedicated their excellent ideas in enhancing students’ thinking process by using Bloom’s Taxonomy in mainly the Cognitive Domain. The writer finally concludes that the levels of thinking processes in the Cognitive Domain(remembering, understanding, applying, analyzing, evaluating, and creating) are in badly needed to be applied to enhance students’ critical thinking.Key words: Bloom’s taxonomy, cognitive domain, critical thinking